Risk assessment of potential rock collapse in Fenghuang Mountain, three gorges reservoir area, China - Cheng, Shi; Dai, Zhenwei; Zhang, Anle; Geng, Jun; Li, Zixuan; Wang, Fen; Huang, Bolin; Zhang, Nan; Jiang, Xiannian (Frontiers in Earth Science, 2024)
On 8 October 2017, persistent heavy rainfall triggered a rock collapse on Fenghuang Mountain in Wuxi Town, located within the Three Gorges Reservoir region of China. Subsequent field investigations and monitoring identified several potentially unstable rock masses in the area, posing a significant threat to the safety of nearby residents and their property. In this study,the Rapid Mass Movement Simulation (RAMMS) numerical tool was used to perform a back analysis of the rock collapse event. The well calibrated numerical model was then used to assess the risk of the potential unstable rock masses in the study area. The rock collapse on Fenghuang Mountain descended rapidly along the slope, with the dislodged material accumulating at the base and obstructing the road at the foot of the slope. Some debris breached the embankment and entered the Daning River. The computed maximum velocity during the rock collapse event was approximately 9.14 m/s, with an average maximum deposit thickness of around 4.48 m. The back-analysis of the rock collapse event closely aligns with the observed failure process and deposit morphology documented through field investigation. Using the well calibrated numerical model, a dynamic analysis was conducted on the potential unstable rock mass. The risk assessment indicates that the potential unstable rock mass is prone to instability, with a high likelihood of a subsequent rockfall under extreme rainfall conditions. The computed average maximum velocity for the potential rockfall is 33.83 m/s, with an average maximum deposit thickness of 2.20 m. The computed maximum impact pressure is about 164 kPa, which would result in significant damage to the road below. Additionally, a maximum wave height of 1.38 m from the surge caused by potential rockfall entering the Daning River was calculated by a semi-empirical model. This research offers a novel approach and methodology for assessing the risk of such hazardous events in similar geological setting globally.